Probing electronic correlations in actinide materials using multipolar transitions - Bradley, J. A.; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2010)
We report nonresonant inelastic x-ray scattering from the semicore 5d levels of several actinide compounds. Dipole-forbidden, high-multipole features form a rich bound-state spectrum dependent on valence electron configuration and spin-orbit and Coulomb interactions. Cross-material comparisons, together with the anomalously high Coulomb screening required for agreement between atomic-multiplet theory and experiment, demonstrate sensitivity to the neighboring electronic environment, such as is needed to address longstanding questions of electronic localization and bonding in 5f compounds.